Waste Minimization Protocols for the Process of Synthesizing Zeolites from South African Coal Fly Ash - Du Plessis, Pieter W. (Materials (Basel), 2013)
Production of a high value zeolite from fly ash has been shown to be an avenue for the utilization of South African fly ash which presently constitutes a huge disposal problem. The synthesis of zeolites Na-P1 and analcime on a micro-scale has been successful and preliminary investigation shows that scale-up synthesis is promising. However, the post-synthesis supernatant waste generated contains high levels of NaOH that may constitute a secondary disposal problem. A waste minimization protocol was developed to reduce the volume of waste generated with a view to enhancing the feasibility of the scale synthesis. Series of experiments were conducted in 100 mL jacketed batch reactors. Fly ash was reacted with 5 Mol NaOH on a 1:1 mass basis during the aging step, followed by hydrothermal treatment in which ultrapure water was added to the slurry. This study shows that by re-introducing the supernatant waste into the experiments in such a way that it supplies the required reagent (NaOH) for the zeolite synthesis, zeolite Na-P1 and analcime can be synthesized. It also shows that the synthesis process can be altered to allow up to 100% re-use of the supernatant waste to yield high value zeolitic products. This study effectively constructed two protocols for the minimization of waste generated during the synthesis of zeolites from South African coal fly ash. This result could be used to establish a basis for legal and environmental aspects involved in the commission of a full-scale plant synthesizing zeolites NaP1 and analcime.